EFEKTIVITAS PENERAPAN MINDFULNESS-BASED COGNITIVE THERAPY (MBCT) PADA INDIVIDU DENGAN OBSESSIVE COMPULSIVE DISORDER (OCD) - Fanza, I Wayan Nathan; Wilani, Ni Made Ari (Essential: Essence of Scientific Medical Journal; Vol 22 No 2 (2025): Volume 22 No. 2 (November 2024 - Maret 2025) Essential: Essence of Scientific Medical Journal, 2025)
Introduction: Obsessive Compulsive Disorder (OCD) is a psychological health disorder that occurs when individuals have excessive anxiety or fear with obsessive thoughts and compulsive behaviors that interfere with activities that will develop into a severe chronic mental disorder. The most widely used intervention today is CBT, however, there are some drawbacks such as the possibility of relapse and lack of long-term effects. Mindfulness-based cognitive therapy (MBCT) is an intervention that trains skills in individuals with openness, awareness without judgment and acceptance of experience in the present moment. MBCT has been proven effective in overcoming symptoms of anxiety and depression. This study aims to determine the effectiveness of MBCT implementation in individuals with OCD. Discussion: The results showed that MBCT was effective in reducing symptoms of OCD symptoms. MBCT was also shown to significantly reduce anxiety and depression in individuals with OCD. MBCT is an acceptable and safe therapy for individuals with OCD. This therapy is also effective as a follow-up therapy to CBT and can be used as the main therapy for individuals with OCD. Conclusion: Mindfulness-based cognitive therapy (MBCT) is quite effective in reducing symptoms and improving skills in individuals with obsessive compulsive disorder (OCD). The intervention was generally acceptable to individuals with OCD as it increased mindfulness. It can be used as a follow-up therapy to reduce residual symptoms from cognitive behavior therapy (CBT) or as an effective primary therapy .